Reducing drug–herb interaction risk with a computerized reminder system - Lin SS; Tsai CL; Tu CY; Hsieh CL (Dove Medical Press, 2015)
Sheng-Shing Lin,1,2 Chiu-Lin Tsai,3 Ching-Yeh Tu,3 Ching-Liang Hsieh2,4,5 1Graduate Institute of Chinese Medicine, College of Chinese Medicine, China Medical University, 2Department of Chinese Medicine, China Medical University Hospital, 3Division of Chinese Medicine, Department of Pharmacy, China Medical University Hospital, 4Graduate Institute of Integrated Medicine, College of Chinese Medicine, China Medical University, 5Research Center for Chinese Medicine and Acupuncture, China Medical University, Taichung, Taiwan Background: Traditional Chinese medicine (TCM) and Western medicine are both popular in Taiwan. Approximately 14.1% of Taiwanese residents use Western drugs and Chinese herbs concurrently; therefore, drug–herb interaction is critical to patient safety. This paper presents a new procedure for reducing the risk of drug interactions.Methods: Hospital computer systems are modified to ensure that drug–herb interactions are automatically detected when a TCM practitioner is writing a prescription. A pop-up reminder appears, warning of interactions, and the practitioner may adjust doses, delete herbs, or leave the prescription unchanged. A pharmacist will receive interaction information through the system and provide health education to the patient.Results: During the 2011–2013 study period, 256 patients received 891 herbal prescriptions with potential drug–herb interactions. Three of the 50 patients who concurrently used ginseng and antidiabetic drugs manifested hypoglycemia (fasting blood sugar level ≤70 mg/dL).Conclusion: Drug–herb interactions can cause adverse reactions. A computerized reminder system can enable TCM practitioners to reduce the risk of drug–herb interactions. In addition, health education for patients is crucial in avoiding adverse reaction by the interactions. Keywords: Traditional Chinese medicine, Western medicine, adverse reaction